2004
DOI: 10.1177/152660280401100104
|View full text |Cite
|
Sign up to set email alerts
|

How Many Patients with Infrarenal Aneurysms are Candidates for Endovascular Repair? The Northern California Experience

Abstract: Fifty-five percent of patients considered for endovascular AAA repair in community hospitals in Northern California met the anatomical selection criteria for the AneuRx stent-graft. Men appeared to be twice as likely to meet the eligibility requirements as women. Unfavorable infrarenal neck anatomy was the primary exclusion criterion for endovascular repair in this community setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(22 citation statements)
references
References 20 publications
0
20
0
2
Order By: Relevance
“…The data from our systematic review do not suggest that the proportion of women morphologically suitable for EVAR has improved since earlier this century. 6,7 However, the operative mortality in both men and women has fallen substantially since a 2010 systematic review, 9 particularly for open repair; although 30-day operative mortality remains almost twice as high in women as in men. Some of the reduction in operative mortality in women might have come at the expense of the high proportion of women (a third) who are assigned to a non-intervention policy; although, the literature on non-intervention policy remains sparse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data from our systematic review do not suggest that the proportion of women morphologically suitable for EVAR has improved since earlier this century. 6,7 However, the operative mortality in both men and women has fallen substantially since a 2010 systematic review, 9 particularly for open repair; although 30-day operative mortality remains almost twice as high in women as in men. Some of the reduction in operative mortality in women might have come at the expense of the high proportion of women (a third) who are assigned to a non-intervention policy; although, the literature on non-intervention policy remains sparse.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 However, data from the large Medicare database in the USA suggest that this relative difference in 30-day mortality between EVAR and open repair is observed for both men and women, even though the absolute mortality was higher in women than men. 8 An earlier systematic review, 9 including studies published by July, 2009, showed that for elective open repairs the operative mortality (30 day or in-hospital) was 7路6% for women versus 5路1% for men.…”
Section: Introductionmentioning
confidence: 99%
“…7 Furthermore, a high percentage of them have severe comorbidities precluding traditional open repair. [8][9][10] Thus, the unmet medical needs to preserve the endovascular management of complex aortic aneurysms urged clinicians and manufactures to develop SGs with fenestrations (holes) or scallops (gaps or valleys in the upper graft fabric margin) to access visceral arteries, called fenestrated SGs, simply to allow extension of the sealing zone indefinitely, limited only by the desire to limit the number of visceral vessels incorporated into the repair.…”
mentioning
confidence: 99%
“…The proximal neck is the segment of aorta above the aneurysm sac. An unfavourable neck anatomy, based on its diameter, length, angulation, morphology, and presence of calcification and mural thrombus, is the most frequent cause of exclusion from EVAR [12]. a) Length: To achieve a good seal and decrease proximal migration and type I endoleak rates, a length of at least 15-mm for infrarenal stent-graft fixation or 10-mm for transrenal stent-graft fixation, with barbs, hooks, or uncovered suprarenal stents, is recommended [13].…”
Section: ) Proximal Neck Of the Aneurysmmentioning
confidence: 99%